2020
DOI: 10.3389/fmars.2020.00641
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dynamic Food Web Modeling to Explore Environmental Drivers of Ecosystem Change on the Kerguelen Plateau

Abstract: Understanding the impacts of climate and fishing on marine systems is important for ecosystem-based management in the Southern Ocean, but can be difficult to evaluate due to patchy data in space and time. We developed the first time-dynamic food web model for the Kerguelen Plateau using Ecopath with Ecosim to explore likely drivers of change in this relatively data-poor region. The Kerguelen Plateau is located at the centre of intersecting frontal systems and is inhabited by one of the largest populations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…While traditionally associated with warmer SST and lower productivity in the eastern tropical Pacific, studies have shown that climatic effects of El Niño are complex and often lead to cooler waters in other regions around the globe (Hermes & Reason, 2005; Reason et al, 2000; Subramaniam et al, 2020). For example, some areas exhibit colder SST and/or higher productivity in El Niño years, whereas others show lagged effects to El Niño‐associated cooling, often linked to bathymetric features and front locations.…”
Section: Methodsmentioning
confidence: 99%
“…While traditionally associated with warmer SST and lower productivity in the eastern tropical Pacific, studies have shown that climatic effects of El Niño are complex and often lead to cooler waters in other regions around the globe (Hermes & Reason, 2005; Reason et al, 2000; Subramaniam et al, 2020). For example, some areas exhibit colder SST and/or higher productivity in El Niño years, whereas others show lagged effects to El Niño‐associated cooling, often linked to bathymetric features and front locations.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, productivity of Patagonian toothfish on the Kerguelen Plateau has been related to oceanographic conditions, where prey availability may decrease because of increased variability in these conditions in coming years (Subramaniam et al, 2020). This has also been suggested for icefish populations that prey on krill (Reid, 2019), for which the area of greatest productivity is expected to move south (Johnston et al, under review).…”
Section: Effects Of Climate Changementioning
confidence: 99%
“…Several studies have used Ecosim to explore the timedynamic variations of Southern Ocean food webs (Surma et al, 2014;Suprenand and Ainsworth, 2017;Dahood et al, 2019;Subramaniam et al, 2020b). This approach fits models from Ecopath to time-series and/or fisheries data for functional groups (Christensen et al, 2008).…”
Section: Whole-of-food Web Modelsmentioning
confidence: 99%